Effectiveness of Creative Problem Solving (CPS) - STEM Learning Model on Students’ Computational Thinking and Digital Literacy Skills in Biotechnology Material - Indriani, Betty; Saptono, Sigit; Mustikaningtyas, Dewi; Yuniastuti, Ari (Universitas Negeri Semarang, 2024)
Computational Thinking (CT) and digital literacy are skills students must possess to adapt and survive amidst the current technological advancements. One way to enhance students’ CT and digital literacy skills is through innovative learning models that align with the material being taught. Biotechnology is one of the subjects that students need to master in Phase E of the Merdeka Curriculum. This study aims to determine the effectiveness of the CPS-STEM learning model on students’ CT and digital literacy skills in biotechnology material. This research was conducted from April to May in the 2023/2024 academic year at three high schools in the Kayen, with a total population of 891 students. The sample used in this study was calculated using the Slovin formula, its 8 classes consisting of 2 control groups (72 students) and 2 experimental groups (217 students). This study is a quasi-experimental design with a pre-test and post-test group design. The STEM approach is integrated with CPS syntax outlined in the teaching module and assisted with student worksheets. CT skills were measured using post-test instruments, while digital literacy skills were measured using questionnaire. Data analysis was conducted to determine the effectiveness of the CPS-STEM learning model on CT skills, calculated using the N Gain test, while digital literacy skills were measured using a Likert scale. The results showed that the CPS-STEM was effective to improve CT skills in the medium category (0.40), whereas the direct instructional learning model was not effective in enhancing CT skills. This study also showed that the CPS-STEM learning model was effective in enhancing digital literacy skills with a percentage increase of 15.25%